Anion‐Functionalized Pillararenes for Efficient Sulfur Dioxide Capture: Significant Effect of the Anion and the Cavity. Issue 57 (18th September 2017) - Lin, Wenjun; Zhou, Xiuyuan; Cai, Jingsong; Chen, Kaihong; He, Xi; Kong, Xueqian; Li, Haoran; Wang, Congmin
Abstract: A series of anion‐functionalized pillararenes were prepared and applied in the capture of SO2 through incorporating an anion with different basicity into pillararenes. A high SO2 absorption capacity up to 15.9 mmol g −1 and excellent reversibility were achieved by tuning the basicity of the anion and the size of the cavity. Spectroscopic investigations and DFT calculations indicated that high SO2 capacity originated from multiple sites interaction between SO2 and the anion, where SO2 chemical absorption was significant strengthened by the cavity, because the anion was confined in the window of the cavity and the window was electron‐deficient. Interestingly, a phase transition occurred during absorption and desorption process. The method proposed in this work provided an efficient strategy for improving gas absorption through a simple functionalization of the supermolecule, which was also very important for some other fields such as polymers and materials. Abstract : Catch me ! A series of anion‐functionalized pillararenes were prepared and applied in the capture of SO2, which exhibited high SO2 capacity and excellent reversibility, where SO2 chemical absorption was strenghened significantly by the cavity.